Сотрудничество семьи и школы – залог успешного решения задач воспитания школьников. - Krasnozhon I. S. (Modern education development: theory, techniques and practice, 2020)
We are the creators of our own health, which in our time must be fought for!
Keywords: вредные привычки; питание; ЗОЖ